Meat Production in a Feedlot System of Zebu—Holstein Steers and Heifers with Dairy Genetics: Productive and Biological Analyses - Gustavo Chamon de Castro Menezes; Sebastião de Campos Valadares Filho; José Reinaldo Mendes Ruas; Edenio Detmann; Arismar de Castro Menezes; Diego Zanett; Lays Débora Silva Mariz; Luciana Navajas Rennó; Jarbas Miguel da Silva Junior (The Scientific World Journal)
The aim of this study was to evaluate the productive and biological efficiency of steers and heifers from dairy genetics in a feedlot system in terms of meat production. Twenty-four steers and 24 heifers at 10 monthes of age, (3/4) Zebu × (1/4) Holstein were utilized. They were distributed over four feedlot times, 30, 60, 90, and 120 days with four replications for each sex, and were slaughtered at the end of each period. The productive and biological analyses were performed through comparative slaughter to determine the body composition. Heifers presented with greater intakes (P<0.05) of dry matter in grams per kg of body weight. Steers presented with a greater (P<0.05) final empty body weight, carcass gain, cold carcass weight, and meat proportion in the carcass; however, heifers presented with a greater subcutaneous fat thickness (P<0.05) and, consequently, a greater (P<0.05) fat proportion in the carcass. We conclude that steers are more efficient in their productive performance than heifers in a feedlot. For the finishing carcass fat cover, heifers need 90 days in the feedlot. The net energy requirements for maintenance are 67 kcal/EBW0.75/d, and the net requirements of energy (NEg) and protein (NPg) for gain can be estimated by the following equations: NEg(Mcal/d)=0.067×EBW0.75×  EBG1.095 and NPg=162×EBG-5.62×RE for the two sexes.